AN ANALYSIS OF DALALAH AL-ALFADH (LEGAL SEMANTICS) IN MAJMA' FIQH AL-ISLAMI FATWAS CONCERNING THE DIGITAL ECONOMY THE RELATIONSHIP BETWEEN ARABIC LINGUISTIC STRUCTURE AND LEGAL CONCLUSIONS - Faisol; Muhammad A'inul Haq (Universitas Kiai Abdullah Faqih Gresik, 2026)
The rapid disruption of the digital economy necessitates adaptive legal responses from Islamic jurisprudence. This study aims to analyze the application of Dalalah Al-Alfadh (legal semantics) in the fatwas of Majma' Fiqh Al-Islami ad-Dawli concerning digital economic instruments, determining how Arabic linguistic structures shape legal conclusions. Employing a qualitative library research design, this study utilizes an interdisciplinary approach that integrates semantics and ushul fiqh (Islamic legal theory). Data were collected from official fatwa documents and analyzed using textual discourse analysis. The results reveal that the fatwa authority actively engages in